Poly(triazine imide) Crystals for Efficient CO2 Photoreduction: Surface Pyridine Nitrogen Dominates the Performance - Liu, Feng; Deng, Jing; Su, Bo; Peng, Kang-Shun; Liu, Kunlong; Lin, Xiahui; Hung, Sung-Fu; Chen, Xiong; Lu, Xue Feng; Fang, Yuanxing; Zhang, Guigang; Wang, Sibo (ACS catalysis, 2025)
Polymeric carbon nitrides (PCNs), usually the melon phase, have been extensively applied as photocatalysts for CO2 reduction; however, their performance is still unsatisfactory. The condensed allotrope, namely, poly(triazine imide) (PTI) with extended conjugation and a crystallized structure, indeed holds more favorable compositional and structural advantages for photocatalytic CO2 reduction but remains to be fully exploited. Herein, hexagonal prism-shaped PTI crystals were synthesized and developed as a high-performance photocatalyst for CO2 reduction. With Co(bpy)3 2+ as a cocatalyst, the PTI crystals exhibit a CO evolution rate of 44 μmol h–1 (i.e., 1467 μmol g–1 h–1) with 93% selectivity, markedly superior to that of the melon counterpart. Moreover, PTI crystals manifest an apparent quantum efficiency of 12.9% at 365 nm, representing the state-of-the-art value by PCN photocatalysts for CO2-to-CO reduction without using noble metals. The surface pyridine N species of PTI are exposed as active sites to dominate CO2 activation and conversion, which, together with the high crystallinity to facilitate charge separation and transport, endows high CO2 reduction efficiency. In situ diffuse reflectance infrared Fourier transform spectroscopy determines the key intermediates during the CO2 reduction reaction and, consequently, constructs the possible reaction mechanism.